Pengaruh Pelaksanaan Kebijakan Pembinaan Siswa Terhadap Manajemen Kesiswaan dalam Mewujudkan Prilaku Disiplin Siswa - Rian Hidayat; Fitrah Abdul Malik (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2022)
The writing of this article aims to determine the effect of the implementation of studentcoaching onstudent management in an effort to realize student discipline behavior in MTs.Al-Fatwa. The writing of the article on the approach method and research technique usedin this study is expected to provide answers to problem solving through collecting fieldda-ta information that describes the factors that relate to the phenomena studied, namely re-garding the variables of Student Development Policy Implementation, Student Develop-ment Management and Student Discipline Behavior. The conclusions obtained in this studyare First, the variable implementation of the student coaching policy shows good criteria,Second, the student coaching management variable shows good criteria, this is evidencedby the average respondent's answer regarding the variable is good. Third, the variable ofstudent discipline behavior shows good criteria, this is evidenced by the average respond-ents' answers regarding these variables. The indicator withthe highest percentage is on the dimension of discipline in obeying school rules, namely students have a lesson schedule. The lowest assessment is found in the discipline dimension following learning and doing assignments.